A first course in the finite element method - Logan, Daryl L. (PWS Engineering, 1986)
Provides a simple, basic approach to the finite element method that can be understood by both undergraduate and graduate students. It does not have the usual prerequisites (such as structural analysis) required by most available texts in this area